Irritable bowel syndrome-like symptoms and health related quality of life two years after Roux-en-Y gastric bypass - a prospective cohort study - Blom-Høgestøl, Ingvild Kristine (BMC Gastroenterol, 2019)
BACKGROUND: Irritable bowel syndrome (IBS) is prevalent in patients with morbid obesity. After Roux-en-Y gastric bypass (RYGB) chronic abdominal pain is common, however the etiology is largely unknown. We aimed to study the change in the prevalence of IBS-like symptoms 2 years after RYGB and possible preoperative predictors of such symptoms. Secondly, to evaluate changes in symptoms of constipation and diarrhea, and Health related quality of life (HRQoL). METHODS: Patients with morbid obesity were included at two obesity centers in South-Eastern Norway. IBS was diagnosed according to the Rome III criteria. Predictors were evaluated in a multivariable logistic regression analysis. RESULTS: Of 307 participants operated with RYGB, 233 (76%) completed the study questionnaires. Preoperatively 27/233 participants (12%) had IBS, 2 years after RYGB 61/233 (26%) had IBS-like symptoms (p < 0.001). Eleven participants with IBS preoperatively (41%) did not report such symptoms after RYGB. New onset IBS-like symptoms was identified in 45/206 (22%) after RYGB. Fibromyalgia, low LDL levels, high vitamin B(1) levels and IBS before RYGB were independent preoperative predictors of IBS-like symptoms at the follow-up visit. Symptom scores for constipation preoperatively and 2 year after RYGB were 1.5 (0.9) and 1.8 (1.2), and for diarrhea 1.4 (0.9) and 1.8 (1.1), respectively (p < 0.001). We observed a significant improvement in the physical component score for all participants. However, participants with new onset IBS-like symptoms had a significant worsening of the mental component score. CONCLUSIONS: The prevalence of IBS-like symptoms doubled 2 years after RYGB, and these symptoms were associated with reduced HRQoL. Preoperative IBS and fibromyalgia were strong predictors of postoperative IBS-like symptoms.